A Reappraisal of Circulating Fetal Cell Noninvasive Prenatal Testing. Issue 6 (June 2019) - Rezaei, Meysam; Winter, Marnie; Zander-Fox, Deirdre; Whitehead, Clare; Liebelt, Jan; Warkiani, Majid Ebrahimi; Hardy, Tristan; Thierry, Benjamin
Abstract : New tools for higher-resolution fetal genome analysis including microarray and next-generation sequencing have revolutionized prenatal screening. This article provides commentary on this rapidly advancing field and a future perspective emphasizing circulating fetal cell (CFC) utility. Despite the tremendous technological challenges associated with their reliable and cost-effective isolation from maternal blood, CFCs have a strong potential to bridge the gap between the diagnostic sensitivity of invasive procedures and the desirable noninvasive nature of cell-free fetal DNA (cffDNA). Considering the rapid advances in both rare cell isolation and low-input DNA analysis, we argue here that CFC-based noninvasive prenatal testing is poised to be implemented clinically in the near future. Highlights: Non-invasive prenatal testing based on circulating cell-free fetal DNA has gained broad clinical acceptance for the detection of common aneuploidies. However, it cannot currently provide information about the full spectrum of chromosomal abnormalities and single gene disorders. While extremely rare, circulating fetal cells (CFCs) in maternal blood have a complete fetal genome. Advances in genomic analysis techniques promise to resolve the issues associated with high coverage testing of the low amount of genomic material available in a single cell. Recently, many technologies have been validated for the enrichment and isolation of rare cells from peripheral blood, paving the way for development of clinically applicable CFC isolation methodologies. Now is the ideal time to reappraise the relevance and use of CFCs in prenatal diagnosis, particularly their clinical scope and benefit.